Application of Organic Fertilizer Cow Dung and Biofertilizer in Shallots (Allium Acalonicum L.) in Lowland - Rastuti Kalasari; Neni Marlina; Marlina Marlina; Nurul Husna; Irnady Irnady (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Lowland has the potential to be developed to plant shallots, given the importance of shallots in meeting the growing needs of the Indonesian people and supported by a high market share, therefore to increase the productivity of shallots in Lowland it is necessary to apply organic cow dung and biofertilizer. The purpose of this study was to determine the best organic cow dung and biofertilizer in increasing the productivity of shallots on land or in lowland. This research was conducted in Seri Tanjung Village, Tanjung Batu District, Ogan Ilir Regency, South Sumatra Province. The layout of the experiment was in polybags using a factorial randomized block design with 8 treatment combinations which were repeated 4 times. Factor 1 is organic cow dung fertilizer, namely 0, 7.5, 15, 22.5 tons/ha. Factor 2 is biofertilizer, namely without and biofertilizer. The highest production (dry weight of plant tubers) was achieved in the application of organic cow dung fertilizer of 15 tons/ha with bio fertilizers, which was 53.56 g/plant.